New product development processes and knowledge transfer in automotive projects: An empirical study. (12th October 2018) - Lee, Nam S.; Ram, Jiwat
Abstract : We report on the process management of a new product development project in Renault Samsung Motors, Inc., which is an international joint venture between Renault and Samsung, and also a part of strategic alliance between Renault and Nissan. The data collected from multiple sources were analyzed using qualitative analysis techniques. The findings show that (a) companies entering into concurrent technology/knowledge transfer by sharing platforms should consider their organizational capabilities carefully before introducing platforms from partner companies. Nevertheless, a company does not have to lower its standard in choosing a platform in order to match its underdeveloped organizational capabilities. Rather, customer expectations and market requirements should be the basis of selecting a platform to be introduced, and (b) developing a similar project organization structure and processes in a strategic alliance is effective in building trust and improving knowledge sharing/transfer between firms and between functions. The study contributes to development of two areas of management theory: (1) management of knowledge, and (2) expertise transfer in alliance/international business new product development projects and intricacies involved in it. Managerially, the implications are that the ownership and control of an international joint venture have a deep impact on the management of organization structure and processes. In turn, these may promote or inhibit effective cooperation and knowledge transfer between partner companies and their functions.